2017
DOI: 10.1007/978-1-4939-6981-4_1
|View full text |Cite
|
Sign up to set email alerts
|

Global Spread of Hemorrhagic Fever Viruses: Predicting Pandemics

Abstract: As successive epidemics have swept the world, the scientific community has quickly learned from them about the emergence and transmission of communicable diseases. Epidemics usually occur when health systems are unprepared. During an unexpected epidemic, health authorities engage in damage control, fear drives action, and the desire to understand the threat is greatest. As humanity recovers, policy-makers seek scientific expertise to improve their "preparedness" to face future events.Global spread of disease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…To date, illness monitoring and vector development efforts that are reliable and integrated have not been widely applied in many countries, especially in tropical Southeast Asian countries. This is also consistent with the increase in sporadic diseases related to the lack of monitoring efforts [13].…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…To date, illness monitoring and vector development efforts that are reliable and integrated have not been widely applied in many countries, especially in tropical Southeast Asian countries. This is also consistent with the increase in sporadic diseases related to the lack of monitoring efforts [13].…”
Section: Introductionsupporting
confidence: 85%
“…The results of Qureshi et al's study showed that humid conditions were significant in postrain (p = 0.024) [19]. The tropics have high humidity and the potential to breed aedes agypti mosquitoes [13]. After sucking blood, Aedes aegypti female mosquitoes then produce eggs.…”
Section: Discussionmentioning
confidence: 99%
“…A GIS is designed to capture, store, manipulate, analyze, manage, optimize, and present a broad spectrum of geographical data relevant to the task at hand. While the healthcare literature is replete with GIS papers, some proving efficacy for highly infectious diseases, such as Ebola (84)(85)(86)(87), Solution 4 lists only those that combined both POC and GIS concepts, especially the analysis of population access in terms of travel time (Figure 8), an important criteria for deciding where to place POCT.…”
Section: Geographic Information Systems (Gis) + Point-of-care Testingmentioning
confidence: 99%
“…Today, with the endless epidemic unfolding in the DRC, should we revisit our tools and strategy of struggle in an ever-changing world? [64].…”
Section: If We Had To Concludementioning
confidence: 99%